Efficient Differentiation of Human Pluripotent Stem Cells to Endothelial Cells. (6th July 2018) - Gu, Mingxia
Abstract: Endothelial cells (ECs) line the interior surface of blood and lymphatic vessels, and play a key role in a variety of physiological or pathological processes such as thrombosis, inflammation, or vascular wall remodeling. Human‐induced pluripotent stem cell (iPSCs)‐derived ECs provide a new opportunity for vascular regeneration and serve as a model to study the mechanism and to screen for novel therapies. We use developmental cues in a monolayer differentiation approach to efficiently generate mesoderm cells from iPSCs via small‐molecule activation of WNT signaling in chemically defined medium for 4 days, and subsequent EC specification using vascular endothelial growth factor and fibroblast growth factor for another 4 days. After 8 days of differentiation, mature ECs are further purified using magnetic‐activated cell sorting for the EC surface marker CD144. These ECs exhibit molecular and cellular characteristics consistent with native ECs, such as expression of specific surface markers, formation of tube‐like structures and acetylated low‐density lipoprotein uptake. © 2018 by John Wiley & Sons, Inc.